Atherosclerosis and Hippocampal Volumes in Older Adults: The Role of Age and Blood Pressure - Alifiya Kapasi; Ana W. Capuano; Melissa Lamar; Sue E. Leurgans; Arnold M. Evia; David A. Bennett; Konstantinos Arfanakis; Julie A. Schneider (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Lower hippocampal volume is associated with late‐life cognitive decline and is an important, but nonspecific marker for clinical Alzheimer's dementia. Cerebrovascular disease may also be associated with hippocampal volume. Here we study the role of intracranial large vessel disease (atherosclerosis) in association with hippocampal volume and the potential role of age, average late‐life blood pressure across all visits, and other factors (sex, apolipoprotein ε4 [APOE ε4], and diabetes). Methods and Results Data came from 765 community‐based older people (91 years old on average at death; 72% women), from 2 ongoing clinical‐pathologic cohort studies. Participants completed baseline assessment, annual standardized blood pressure measurements, vascular risk assessment for diabetes, and blood draws to determine APOE genotype, and at death, brains were removed and underwent ex vivo magnetic resonance imaging and neuropathologic evaluation for atherosclerosis pathology and other cerebrovascular and neurodegenerative pathologies. Linear regression models examined the association of atherosclerosis and hippocampal to hemisphere volume ratio and whether age at death, blood pressure, and other factors modified associations. In linear regression models adjusted for demographics and neurodegenerative and other cerebrovascular pathologies, atherosclerosis severity was associated with a lower hippocampal to hemisphere volume ratio. In separate models, we found the effect of atherosclerosis on the ratio of hippocampal to hemisphere volume was attenuated among advanced age at death or having higher systolic blood pressure (interaction terms P≤0.03). We did not find confounding or interactions with sex, diabetes, or APOE ε4. Conclusions Atherosclerosis severity is associated with lower hippocampal volume, independent of neurodegenerative and other cerebrovascular pathologies. Higher systolic blood pressures and advanced age attenuate associations.